The Many Faces of Strategic Voting Tactical Behavior in Electoral Systems Around the World - Aldrich, John; Blais, André; Stevenson, Laura B. (University of Michigan Press, 2018)
Voters do not always choose their preferred candidate on election day. Often they cast their ballots to prevent a particular outcome, as when their own preferred candidate has no hope of winning and they want to prevent another, undesirable candidate's victory; or, they vote to promote a single-party majority in parliamentary systems, when their own candidate is from a party that has no hope of winning. In their thought-provoking book The Many Faces of Strategic Voting, Laura B. Stephenson, John H. Aldrich, and André Blais first provide a conceptual framework for understanding why people vote strategically, and what the differences are between sincere and strategic voting behaviors. Expert contributors then explore the many facets of strategic voting through case studies in Great Britain, Spain, Canada, Japan, Belgium, Germany, Switzerland, and the European Union.